Proyecto de factibilidad para la creación de un centro asistencial y cuidado de adultos mayores en la ciudad de Loja - Poma Coronel, Gladis Maritza (2015)
The research whose objective was to conduct the Feasibility Project for the creation of a hospital and care seniors in the city of Loja, for which the corresponding studies were performed allowing to determine the feasibility of the company. As the attention of Aging a critical point in our society for many aspects that have been analyzed in the present investigation, one of the main problems are the high cost of private health establishments, while the public is negative lamentable care received by the elderly and the poor have to endure the poor quality of care staff working in these health institutions. For all these reasons I consider it important to implement a Care Centre for the Elderly in the city of Loja, for this important group of society has a place with all the equipment, technology and qualified personnel and with costs accessible to this group in our society. This research was carried out following the scheme in force at the National University of Loja, Theoretical Framework, a product of the research literature are highlighted where the conceptual aspects of the study described. In the market study, 395 surveys were applied corresponding to 29,609 adults over 60 years old, knowing the actual demand the same services is 22,500; these results have an effective demand for services 19,800, likewise the real deal is estimated at 7,100 services which gives us an unmet demand for 12,700 people demanding the service. The Technical Study was mainly established the macro and micro location which via a locational matrix was determined that the site will work the company is in the La Banda field, size and engineering company, its installed capacity of 8,890, and the capacity utilization in the first year of life of the project is 6,960 services or what is the same 78%. In the Administrative study it found that the company is established as a limited liability company; likewise the internal structure was determined together with the different types of charts, also the functions of each person that makes up the Unit were detailed. Financial Study With economic conditions for the feasibility so much so that for the investment needed to implement the project is $ 48,778.73 of which 58% will be financed with equity and the remaining 42% through is evaluated a bank credit. The financial analysis NPV (net present value) of 46,621.77 was obtained; IRR (internal rate of return) of 30.22%, the PRC (capital recovery period) is 3 years 0 months and one day respectively. As for the RBC (benefit-cost ratio) it was determined that for every dollar invested company earns 0.15 cents. With regard to sensitivity analysis we pointed out that the project supports increased costs of 15.26% and a decrease in revenue of 12.13%, respectively. Finally he completed all feasibility studies of the project was determined and its implementation are recommended. Following the conclusions, recommendations and bibliography respective annexes are presented